Preliminary evaluation of tolerance and local effectiveness of extracranial stereotactic radiosurgery and radioablation in lung tumor patients - Idasiak, Adam; Rutkowski, Roman; Grządziel, Aleksandra; Suwiński, Rafał (Contemporary Oncology/Współczesna Onkologia, 2005)
Purpose: To evaluate treatment tolerance and tumor response in extracranial stereotactic radiosurgery and radioablation in lung tumor patients. Materials and methods: 35 patients (30 males and 5 females) with median age of 61 years, with lung tumors (primary lung cancer n=13, local recurrences of lung cancer n=9, lung metastases n=13) were treated using extracranial stereotactic radiation (ESR). VAC-LOK cushion system was used for immobilization. Total doses applied using ESR ranged from 8 Gy to 20 Gy, and were delivered using 3-10 beams. Patients were treated with radical (n=22) and palliative intention (n=13). Treatment toxicity was evaluated according to the RTOG/EORTC system. Tumor response was evaluated using the RECIST scale. Survival of the patients was analyzed using the Kaplan-Meier method. Results: The therapy was performed with no significant adverse symptoms. The most frequent acute reaction was fever which lasted for 1-2 days after therapy. Seventeen patients (48%) responded to therapy, in 15 patients (43%) the disease progressed, 3 patients (9%) were not evaluated for tumor response. One-year actuarial progression-free survival was 36% and one-year overall survival was 46%. Irradiated volume, radiation dose and dose per fraction did not significantly influence survival. Conclusions: Stereotactic irradiation of targets in the lung is a new attractive treatment modality with acceptable acute toxicity and local effectiveness. Based on our initial experience the role of extracranial stereotactic radiotherapy in the curative and palliative management for lung tumor should be further investigated.